Spin conductivity of the two-dimensional ferroquadrupolar Heisenberg model. (February 2016) - Lima, L.S.
Abstract: We use the SU(3) Schwinger׳s boson theory to study the spin transport in the S =1 two-dimensional ferroquadrupolar Heisenberg model in the square lattice. We calculate the spin conductivity σ ( ω ) and analyzed the behavior of the AC and DC spin conductivities. The model presents a bilinear and biquadratic exchange interactions. Our results show that the system is an ideal spin conductor for T > 0, because Drude׳s weight D S (which represents the DC conductivity) is non zero for T > 0 and the AC conductivity given by σ reg ( ω ) tends to the infinity when ω → 0 which also correspond to the DC limit. Abstract : Highlights: We employ SU(3) Schwinger boson formalism together with the Kubo formula to calculate the spin conductivity. We find the behavior of AC conductivity σ reg ( ω ) where the region Δ ω where the AC conductivity tends to infinity when ω → 0 . We determine the behavior of the spin stiffness D c with T .